An equivalent soil mass procedure for monitoring soil organic carbon in multiple soil layers - Wendt, J.; Hauser, S. (Wiley, 2013)
Soil carbon stocks are commonly quantified at fixed depths as the product of soil bulk density, depth and organic carbon (OC) concentration. However, this method systematically overestimates OC stocks in treatments with greater bulk densities such as minimum tillage, exaggerating their benefits. Its use has compromised estimates of OC change where bulk densities differed between treatments or over time periods. We argue that its use should be discontinued and a considerable body of past research re-evaluated. Accurate OC estimations must be based on quantification in equivalent soil masses (ESMs). The objective of this publication is to encourage accurate quantification of changes in OC stocks and other soil properties using ESM procedures by developing a simple procedure to quantify OC in multiple soil layers. We explain errors inherent in fixed depth procedures and show how these errors are eliminated using ESM methods. We describe a new ESM procedure for calculating OC stocks in multiple soil layers and show that it can be implemented without bulk density sampling, which reduces sampling time and facilitates evaluations at greater depths, where bulk density sampling is difficult. A spreadsheet has been developed to facilitate calculations. A sample adjustment procedure is described to facilitate OC quantification in a single equivalent soil mass layer from the surface, when multiple-layer quantification is not necessary.